Two-stage surgical treatment of infected pacemaker leads and tricuspid valve endocarditis occurring 20 years after implantation - (:unkn) unknown (My University, 2007)
Infective endocarditis associated with permanent transvenous pacing is a rare but serious complication. A 64-year-old man was referred to our hospital with fever of unknown origin. Despite repeated antibiotic therapies, he sustained fever for a year without any documented infectious foci, and all blood cultures were negative. He had a history of permanent transvenous pacemaker (PM) implantation 20 years before, followed by two subsequent reimplantation procedures due to lead detachment. After unsuccessful efforts of percutaneous removal, all PM leads and wires were left in place. On admission, he was in sinus rhythm and the PM leads were completely dysfunctional. His temperature was above 38.5°C. Transthoracic echocardiography findings were normal except for mild to moderate tricuspid insufficiency. Transesophageal echocardiography revealed a large vegetation, 19x13 mm in size, attached to the pacemaker leads, and multiple tiny vegetations over the anterior and septal leaflets. There was also moderate tricuspid insufficiency. Under cardiopulmonary bypass and aortic cross-clamping, infected pacemaker wires were removed and infected anterior and septal leaflets of the tricuspid valve were excised. Cultures from the PM wires and leaflets revealed methicillin-resistant Staphylococcus epidermidis. After 10 days of specific antibiotic therapy, tricuspid valve replacement was performed. During a follow-up of 17 months, the patient remained free of any cardiac events or fever.
Keywords: Echocardiography, transesophageal; Endocarditis, bacterial/surgery; Equipment contamination; Pacemaker, artificial/adverse effects; Staphylococcal infections/surgery